Arm swing as a potential new prodromal marker of Parkinson's disease. Issue 10 (6th October 2016) - Mirelman, Anat; Bernad‐Elazari, Hagar; Thaler, Avner; Giladi‐Yacobi, Eytan; Gurevich, Tanya; Gana‐Weisz, Mali; Saunders‐Pullman, Rachel; Raymond, Deborah; Doan, Nancy; Bressman, Susan B.; Marder, Karen S.; Alcalay, Roy N.; et al.
ABSTRACT: Background: Reduced arm swing is a well‐known clinical feature of Parkinson's disease (PD), often observed early in the course of the disease. We hypothesized that subtle changes in arm swing and axial rotation may also be detectable in the prodromal phase. Objective: The purpose of this study was to evaluate the relationship between the LRRK2‐ G2019S mutation, arm swing, and axial rotation in healthy nonmanifesting carriers and noncarriers of the G2019S mutation and in patients with PD. Methods: A total of 380 participants (186 healthy nonmanifesting controls and 194 PD patients) from 6 clinical sites underwent gait analysis while wearing synchronized 3‐axis body‐fixed sensors on the lower back and bilateral wrists. Participants walked for 1 minute under the following 2 conditions: (1) usual walking and (2) dual‐task walking. Arm swing amplitudes, asymmetry, variability, and smoothness were calculated for both arms along with measures of axial rotation. Results: A total of 122 nonmanifesting participants and 67 PD patients were carriers of the G2019S mutation. Nonmanifesting mutation carriers walked with greater arm swing asymmetry and variability and lower axial rotation smoothness under the dual task condition when compared with noncarriers ( P < .04). In the nonmanifesting mutation carriers, arm swing asymmetry was associated with gait variability under dual task ( P = .003). PD carriers showed greater asymmetry and variability of movement than PD noncarriers, even after controlling for disease severity ( P < .009). Conclusions: The G2019S mutation is associated with increased asymmetry and variability among nonmanifesting participants and patients with PD. Prospective studies should determine if arm swing asymmetry and axial rotation smoothness may be used as motor markers of prodromal PD. © 2016 International Parkinson and Movement Disorder Society